The Impact of Financial and Tax Reporting Incentives on Option Grants to Canadian CEOs* - KLASSEN, KENNETH J.; MAWANI, AMIN (Contemporary Accounting Research, 2000)
Abstract This study explores the effects of financial and tax reporting incentives on options granted to chief executive officers in Canada. Extant studies with a similar objective (Yermack 1995; Matsunaga 1995) explore predominantly nonqualified U.S. option grants that are deductible to the extent that the options are in the money at the time of exercise. In contrast, Canadian firms do not get a tax deduction for their stock option grants at any time. In both countries, no expense is recorded for financial reporting purposes. As a result, the financial reporting and tax reporting trade‐off is more pronounced in the Canadian setting of this study compared with the U.S. setting. We measure option granting behavior as the ratio of the Black‐Scholes value of stock option grants to the sum of cash compensation and the value of stock option grants. Using a sample of 806 firm‐year observations during the period 1993‐95, we find that observed option grants are significantly correlated with proxies for short‐run financial reporting incentives. We also find evidence that option granting behavior is correlated with proxies for tax incentives.